Proceedings of the 6th International Conference on Foundations of Digital Games 2011
DOI: 10.1145/2159365.2159367
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of social gameplay macros in the Foldit cookbook

Abstract: As games grow in complexity, gameplay needs to provide players with powerful means of managing this complexity. One approach is to give automation tools to players. In this paper, we analyze an in-game automation tool, the Foldit cookbook, for the scientific discovery game Foldit. The cookbook allows players to write recipes that can automate their strategies. Through analysis of cookbook usage, we observe that players take advantage of social mechanisms in the game to share, run, and modify recipes. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 13 publications
0
18
0
5
Order By: Relevance
“…Additionally, there is the advantage of an untapped expertise of the crowd. Even though these crowdsourced projects are not asking scientific experts to participate, participants have been found to be experts at puzzles and problem solving, which would make them specifically adept at solving protein structures in Foldit 12,13,[17][18][19]21 and solving multiple sequence alignment with Phylo. 23 Presumably, among members of the public one could find experts at many different tasks, especially when the task is presented as a game that benefits science.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is the advantage of an untapped expertise of the crowd. Even though these crowdsourced projects are not asking scientific experts to participate, participants have been found to be experts at puzzles and problem solving, which would make them specifically adept at solving protein structures in Foldit 12,13,[17][18][19]21 and solving multiple sequence alignment with Phylo. 23 Presumably, among members of the public one could find experts at many different tasks, especially when the task is presented as a game that benefits science.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these used Foldit, an online game that allows users to manipulate the three-dimensional structures of proteins in order to find the most likely tertiary structure. 12,13,[17][18][19]21 Also described was the online game Phylo, where users moved colored blocks representing different nucleotides of a gene promoter sequence around on screen in order to make the most parsimonious phylogenetic tree. 23 …”
Section: Problem Solvingmentioning
confidence: 99%
“…In 2011, it was reported that Foldit players managed to uncover a protein folding structure underlying the HIV enzyme within 3 weeks, a puzzle that had stumped professional researchers for decades. 22 Following on from this discovery, researchers have studied Foldit players to try to understand how they codify their strategies, share them and improve them Cooper et al, 2011].…”
Section: Creativitymentioning
confidence: 99%
“…A group of Foldit gamers managed to uncover the protein structure of a HIV enzyme that had previously stumped scientists for over a decade (Cooper et al, 2011). Tinati et al (2015) suggest that citizen-led discovery is facilitated by task workflows which encourage discussion and timely support from science team members.…”
Section: Creativity In Citizen Cybersciencementioning
confidence: 99%
“…This can result in new scientific discoveries that may not have been possible if not for the creative thinking of volunteers. Famous examples of this include Galaxy Zoo's "Pea Hunt" (Cardamone et al, 2009) and Foldit's HIV enzyme discovery (Cooper et al, 2011). However, could there be other kinds of creative outputs from volunteers that are less ground-breaking, but also valuable for a project's success?…”
Section: Introductionmentioning
confidence: 99%